2019
DOI: 10.30542/jcems.2019.02.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Non-Veterinary Emergency Care of Law Enforcement Canines at Mass Gathering Events: A Pilot Training Course for Collegiate-Based EMS Providers

Abstract: in a specific location for a specified period of time. 2 In particular, law enforcement canines (LEK9s) are now frequently included on security teams at MGEs. LEK9s have numerous assignments, including explosives and narcotics detection, patrol, tracking, apprehension and arrest, and search and rescue. Their versatility stems from their keen sense of smell, ability to navigate inaccessible areas, and ability to search a given area approximately 50 times faster than a human. [3][4][5][6][7] LEK9s working at mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The pharmacokinetics of 4 mg IN atomised naloxone have been described 21 . A training program for emergency care in law enforcement canines which included guidelines for opioid reversal, suggested a dose of 2–4 mg per 25 kg animal 22 . A recent study has demonstrated that transbuccal naloxone impregnated swabs in dogs were capable of achieving plasma naloxone levels comparable to a 0.4 mg IM injection 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetics of 4 mg IN atomised naloxone have been described 21 . A training program for emergency care in law enforcement canines which included guidelines for opioid reversal, suggested a dose of 2–4 mg per 25 kg animal 22 . A recent study has demonstrated that transbuccal naloxone impregnated swabs in dogs were capable of achieving plasma naloxone levels comparable to a 0.4 mg IM injection 23 …”
Section: Discussionmentioning
confidence: 99%
“…21 A training program for emergency care in law enforcement canines which included guidelines for opioid reversal, suggested a dose of 2-4 mg per 25 kg animal. 22 A recent study has demonstrated that transbuccal naloxone impregnated swabs in dogs were capable of achieving plasma naloxone levels comparable to a 0.4 mg IM injection. 23 In this case, considering the effective response to IV naloxone when given in hospital, it is likely that the intramuscular naloxone administered at home was inadequately dosed, inappropriately administered or mishandled.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 99%